Ад’єктивне лексико-семантичне мікрополе "байдужість” у сучасній англійській мові - Гончар, Катерина; Троцюк, Аїда; Honchar, Kateryna; Trotsiuk, Aida (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Досліджується лексико-семантичне мікрополе прикметників, що виражають значення байдужості в англійській мові. Аналіз проводиться на основі лексикографічних джерел. Це мікрополе моделюється на основі компонентного аналізу лексичних одиниць із значенням «байдужий», що демонструє наявність у семантичній структурі досліджуваних лексем архісеми «незацікавлений, неемоційний». Наведена архісема є домінантою ад’єктивного мікрополя байдужості й присутня, більшою чи меншою мірою, у визначеннях усіх досліджених лексем цього поля. Категоріальна семантика прикметника – це вираження ознаки предмета, тому прикметникове лексико-семантичне мікрополе реалізує емоційний стан об’єкта «байдужість». Аналізоване лексико-семантичне мікрополе є складовою частиною номінативного макрополя байдужості. Структура мікрополя складається з ядра, приядерної та периферійної зон, межі між якими розмиті, оскільки окремі лексико -семантичні варіанти можуть бути конституентами обох зон. Ядром ад’єктивного лексико-семантичного мікрополя байдужості виступає прикметник indifferent, який є частотним, максимально абстрактним, з агальновідомим, небагатозначним та стилістично нейтральним. До приядерної зони відносяться синоніми прикметника indifferent або прикметники, які у своїх визначеннях містять експліцитно виражену архісему «незацікавлений, неемоційний». До периферії відносяться ті лексеми, які втратили деякі з основних характеристик та набули нових кваліфікативних значень, але містять у своїх дефініціях родову ознаку.The article deals with the lexico-semantic microfield of adjectives expressing the meaning “indifference” in modern English. The analysis is based on lexicographical sources. The investigated lexico-semantic microfield is a constituent part of the nominative macrofield of indifference. The structure of the adjectival microfield consists of a nucleus, co-nuclear and peripheral areas, boundaries between which are blurred, as an individual lexico -semantic variant can be a constituent of several zones. The analyzed microfield is reconstructed on the basis of semantic analysis of lexical units with a meaning “indifferent”. The nucleus of the investigated adjectival lexico -semantic microfield is an adjective “indifferent”, as it possesses distinct features of the field dominants (highly frequent, abstract, stylistically neutral) and can replace any of the members of the paradigm for it is the main representative of this paradigm. Componential analysis of the nuclear lexeme makes it possible to single out the archiseme of the researched microfield “disinterested, unemotional”. This archiseme is a field identifier and its notion is more or less presented in the definitions of all units of adjectival microfield of indifference. Co-nuclear zone consists of the synonyms of indifferent and other lexemes, definitions of which contain explicitly expressed archiseme which is “disinterested, unemotional”. Close periphery zone of the adjectival lexico-semantic microfield of indifference consists of those units that are slightly different in their meaning from the nuclear lexeme. Adjectives that belong to the close periphery may be classified into three groups according to the common semantic characteristic: a) those that have the seme “lacking emotions and other feelings”; b) lexical units grouped by the seme “not showing any concern or sympathy to others” and c) the adjectives with the common seme “not affected/not influenced by others”. Lexical units that have lost some main features and gained new qualifying meanings belong to the remote periphery of the investigated field. They are classified according to the two common semes: “not wanting or wishing to do anything” and “not willing to make any effort or improve anything”. Nominative units with low frequency and limitation in usage refer to the marginal layer of the adjectival lexico-semantic microfield of indifference.
Adjectival Lexico-Semantic Microfield of Indifference in Modern English
Keywords: лексико-семантичне мікрополе; архісема; ядро; кваліфікативна сема; байдужість; компонентний аналіз; lexico-semantic microfield; archiseme; nucleus; qualifying seme; indifference; componential analysis